2012
DOI: 10.1111/j.1471-0528.2012.03430.x
|View full text |Cite
|
Sign up to set email alerts
|

Sildenafil citrate improves perinatal outcome in fetuses from pre‐eclamptic rats

Abstract: Objective To evaluate perinatal outcome after sildenafil citrate (SC) administration at the onset of pregnancy in a rat preeclampsia model.Design In vivo animal experimental study.Setting Fundació n IVI-Instituto Universitario IVI, Valencia, Spain.SampleControl and pre-eclampsia-induced pregnant Wistar rats exposed to chronic SC administration.Methods We evaluated the use of SC, which was tested as a potential therapeutic tool to maintain vasodilatation in complicated pregnancies. We have demonstrated previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
40
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(44 citation statements)
references
References 57 publications
(137 reference statements)
2
40
2
Order By: Relevance
“…Furthermore, sildenafil treatment significantly decreased the uterine artery resistance index of sFlt1 mice with normalization of blood flow to the gravid uterus ( Figure 5G; P < 0.05). These data are consistent with recent publications suggesting the efficacy of sildenafil in other models of fetal growth restriction or preeclampsia (31)(32)(33)(34), and support the potential to use sildenafil as a novel therapy to alleviate signs and symptoms of preeclampsia. However, the safety and potential benefit of this therapy to the fetus have not been explored.…”
Section: Resultssupporting
confidence: 81%
“…Furthermore, sildenafil treatment significantly decreased the uterine artery resistance index of sFlt1 mice with normalization of blood flow to the gravid uterus ( Figure 5G; P < 0.05). These data are consistent with recent publications suggesting the efficacy of sildenafil in other models of fetal growth restriction or preeclampsia (31)(32)(33)(34), and support the potential to use sildenafil as a novel therapy to alleviate signs and symptoms of preeclampsia. However, the safety and potential benefit of this therapy to the fetus have not been explored.…”
Section: Resultssupporting
confidence: 81%
“…Phosphodiesterase type-5 messenger RNA is expressed in the uterus and placenta (14). Interestingly, recent studies have shown that sildenafil can be used successfully to correct a thin endometrium and reduce recurrent implantation failure (15,16), and therapeutically for intrauterine growth restriction (IUGR) and pre-eclampsia (17,18). Others have refuted the suggested benefits of sildenafil as a treatment for preeclampsia (19,20), but the intervention might have been applied too late to reverse endothelial damage and placental dysfunction.…”
mentioning
confidence: 94%
“…Sildenafil treatment was found to improve fetal growth and normalize umbilical artery Doppler waveforms in the preeclamptic catechol-O-Methyl Transferase knockout (COMT −/− ) mouse model 5 . However, sildenafil administration in the L-NAME model of intrauterine growth restriction and preeclampsia have yielded mixed results with one study reporting that sildenafil treatment resulted in a decrease in pup weight 10 and another that demonstrated sildenafil improved both maternal and fetal outcomes 11 . Sildenafil treatment was not able to prolong pregnancy in preeclamptic women in a small clinical trial 8 ; however, this may have been due to late administration and suboptimal dosing.…”
Section: Introductionmentioning
confidence: 99%